Pengaruh Tingkat Kesehatan Bank dengan Menggunakan Metode Risk Based Bank Rating terhadap Nilai Perusahaan pada Perusahaan Perbankan dalam Indeks Infobank15 yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Alisya Syaila Salsabila; Azib; Lasmanah (Bandung Conference Series: Business and Management, 2024)
Abstract. The research aims to evaluate the impact of bank health on company value on the Infobank15 banking index on the BEI from 2018 to 2022. Bank health is evaluated by utilizing the RBBR methodology, which includes the non performing loan, loan to deposit ratio, good corporate governance, return on assets, net interest margin, and capital adequacy ratio to company value (price to book value). Purposive sampling was used in research and panel data regression data processing methods with the Eviews 10 program. The findings show that the overall level of bank health has a significant positive impact on company value. Separately, return on assets has a significant positive impact on company value, while non performing loans, good corporate governance, and net interest margin have an insignificant positive impact on company value. The loan to deposit ratio and capital adequacy ratio have an insignificant negative impact on company value. Abstrak. Penelitian bertujuan mengevaluasi dampak kesehatan bank pada nilai perusahaan pada perbankan indeks Infobank15 di BEI tahun 2018 sampai 2022. Kesehatan bank dievaluasi dengan memanfaatkan Risk Based Bank Rating yang mencakup Non Performing Loan, Loan to Deposit Ratio, Good Corporate Governance, Return On Asset, Net Interest Margin, serta Capital Adequacy Ratio terhadap nilai perusahaan (Price to Book Value). Purposive sampling dimanfaatkan dalam penelitian dan metode pengolahan data regresi data panel dengan program Eviews 10. Temuan menampilkan bahwa tingkat kesehatan bank secara keseluruhan, berdampak positif signifikan pada nilai perusahaan. Secara terpisah, Return on Asset berdampak positif signifikan pada nilai perusahaan, sedangkan Non Performing Loan, Good Corporate Governance, dan Net Interest Margin berdampak positif tidak signifikan pada nilai perusahaan. Adapun Loan to Deposit Ratio serta Capital Adequacy Ratio berdampak negatif tidak signifikan pada nilai perusahaan.